2018
DOI: 10.1007/s00384-018-2994-x
|View full text |Cite
|
Sign up to set email alerts
|

Loop-ileostomy reversal—patient-related characteristics influencing time to closure

Abstract: PurposeTo identify factors associated with timing of stoma reversal after rectal cancer surgery in a large Swedish register-based cohort.MethodsThree thousand five hundred sixty-four patients with rectal cancer who received a protective stoma during surgery in 2007–2013 were identified in the Swedish colorectal cancer register. Time to stoma reversal was evaluated over a follow-up period of one and a half years. Factors associated with timing of stoma reversal were analysed using Cox regression analysis. Rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…The reversal rate in this study was 83%. Compared to other studies, the reversal rate in the present study was normal to high [9,26,27]. Gustafsson et al used a purely registry-based method and showed that the overall reversal rate in Sweden 2007-2013 was 82.9% which is very similar to the reversal rate in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The reversal rate in this study was 83%. Compared to other studies, the reversal rate in the present study was normal to high [9,26,27]. Gustafsson et al used a purely registry-based method and showed that the overall reversal rate in Sweden 2007-2013 was 82.9% which is very similar to the reversal rate in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies, including ours, have been designed using a follow-up period based on this definition. A previous study published by our research group had a follow-up time of 18 months after stoma creation [9]. However, in the present study, 17 of 273 stomas were reversed after 18 months.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations